The role of monitoring and evaluation in six South African reading programmes. Issue 4 (23rd December 2016) - Grigg, Denver; Joffe, Jenna; Okeyo, Alicia; Schkolne, Debbie; van der Merwe, Nicola; Zuma, Mlungisi; Mulenga, Chao; Boodhoo, Adiilah; Louw-Potgieter, Joha
Abstract: In this article we focus on six reading programmes and ask: Do these programmes work insofar as they improve the reading ability of programme participants? We apply programme evaluation methods and content to these programmes to answer this question. Specifically, we use an approach that identifies the following five different levels of evaluation, namely: programme need; programme theory; programme process and implementation; programme outcome and impact; and programme cost and efficiency. We then add appropriate evaluation questions and research designs applicable to each level. We conclude by providing suggestions to reading programme staff on how to improve monitoring (data collection) in order to strengthen the evaluability of their reading programmes.